Deconstruction reassigned? 'The child', antipsychology and the fate of the empirical. (August 2015) - Bradley, Benjamin S
I approach the achievements of Burman's Deconstructing Developmental Psychology (DDP) by contrasting them with: (a) the (non-)'deconstructive' work of Foucault; and (b) Burman's other critical writings. Questions are thus raised about DDP's stance to antidevelopmentalism, antipsychology, deconstruction and the cultural specificity of critique, thereby accentuating the significance of DDP's commitment to feminism. Following consideration of DDP's status as commodity and textbook, I vex the issue of 'evidence' for the central claim in DDP, that developmental psychology (negatively) affects the lives of women and children. I conclude that DDP's key antipsychological contribution is best conceived as having constructed an Other of critique that is far more imposing than the academic sub-discipline of 'developmental psychology' that it ostensibly addresses. In this way, developmental psychology becomes just one part of the (sub)culture(s) that sustain it: hence the futility of setting up developmental psychology as the 'cause' of deleterious 'effects' in the surrounding culture. Beyond this, the second edition of DDP hints at a new role for empirical research when discussing psychologists who work to advocate the rights of children, women and the oppressed. I argue that such political aims are best realised when research with children is framed as an ethical, not an epistemological, practice.